2016
DOI: 10.1136/gutjnl-2015-310239
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of TLR9 promoter variants on spontaneous clearance of HCV infection

Abstract: promoter SNPs are associated with the natural course of HCV infection and show higher transcriptional activities. Our results imply the DNA sensor TLR9 in natural immunity against the RNA virus, HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
(44 reference statements)
6
22
0
Order By: Relevance
“…The minor C allele of rs187084 led to significantly lower expression of protective cytokines IFN- γ and TNF- α than the T allele [ 35 ]. In addition, rs187084 C allele increased the transcriptional activity of TLR9 and provoked a higher level of gene expression [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The minor C allele of rs187084 led to significantly lower expression of protective cytokines IFN- γ and TNF- α than the T allele [ 35 ]. In addition, rs187084 C allele increased the transcriptional activity of TLR9 and provoked a higher level of gene expression [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that rs179008 SNP is truly protective for CHB, our study needs to be repeated in a larger cohort. This cohort preferably should also contain patients spontaneously clearing the disease, similar to a recent study performed on TLR9 SNPs in HCV disease progression (Fischer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The T Ag locus of Merkel cell polyomavirus blocked the C/EBPb transactivator, which also regulated TLR9 transcription (29). Recently, Fischer et al (19) showed that TLR9 promoter SNPs associated with natural clearance of HCV infection showed higher transcriptional activities. We previously showed that TLR9 expression on pDCs, as well as TLR9-mediated secretion of IFN, was impaired by HBV (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that oncoviruses such as HPV16, EBV, and hepatitis C virus (HCV) downregulate TLR9 transcription using NF-kB, which is a negative regulator of TLR9 transcription (12,13,19). We hypothesized that HBV used the same mechanism to block TLR9 transcription in human B cells.…”
Section: Hbv Uses Hbsag To Block Creb Phosphorylation and Binding To mentioning
confidence: 97%